LYRICAL NARRATIVE AND ITS SOCIO-PSYCHOLOGICAL FOUNDATIONS - Jumaniyazova, Dinora (SCIENCE and SOCIETY, 2026)
This article presents a scientific and theoretical analysis of narrative poetry and its poetics in Uzbek literature. The problem is examined through specific examples of the emergence of folklore in poetry, as well as the phenomenon of stylization and modification of literary types and genres.